Building institutions to serve agriculture : a summary report of the C.I.C.-A.I.D. rural development project - Moseman, Albert H. (LaFayette, Indiana. Committee on Institutional Corporation Purdue University, 1968)
This publication contains papers presented at a symposium organised by the Section on Agriculture of the American Association for the Advancement of Sciences held in Cleveland, Ohio on 29th and 30th December, 1963. The symposium focused on characteristics of agricultural systems in emerging nations; research to devise and adapt innovations; education and development of human resources; and establishing indigenous institutions to serve advancing agriculture.
lje 16/06/17
Loans
Keywords: Agriculture; Research; Developing countries